The Relationship of Radiographer’s Level of Knowledge and Concerns to Patients on Radiation Protection at The Radiological Installation of Dr. R.M Djoelham Binjai Hospital - Michael, Michael (PT Inovasi Pratama Internasional, 2023)
Radiation used in radiology installations needs to consider the risks that occur when it comes to radiographers, patients and the surrounding environment. Therefore, they need to receive protection from radiation. Radiographer at RSUD Dr. R.M. Djoelham Binjai still makes many mistakes in radiation protection. The radiographer's actions prove that his awareness of radiation protection is still low. The aim of this research is to find out whether there is a relationship between radiographers' knowledge and concern for patients regarding radiation protection in the Radiology Installation at Dr. RSUD. R.M. Djoelham Binjai. The research population was all radiographers in the Radiology Installation at Dr. R.M. Djoelham Binjai and the sample were 7 active radiographers who were on duty at the installation. Active radiographers who were on duty at the Radiology Installation at Djoelham Binjai Regional Hospital. The research used is quantitative with an observational survey approach. Based on the results of calculating the correlation between knowledge and the radiographer's concern for protection, a significance value was obtained, namely 0.392 > 0.05, which means there is no significant correlation. From these results it can be concluded that there is no relationship between the level of knowledge and the radiographer's concern for patients regarding radiation protection.